Magnetic resonance relaxation measurements using open-geometry sensors to assess the clog state of constructed wetlands - Hughes-Riley, Theodore; Webber, John Beau; Newton, Michael Ian; Morris, Robert H. (Diffusion Fundamentals, 2014)
Monitoring the T1 relaxation of wetland clog matter has previously been identified as a gauge of its clogged state [1]. Magnetic resonance (MR) sensors explored in other work have typically been of a bore-whole configuration, which may not be ideal in a wetland environment where the sensitive volume of the sensor may become physically clogged and therefore inoperable. This work investigates two open-geometry sensor designs and a short study is presented to determine the suitability of the sensors for monitoring the clog state of wetlands. It was shown that a bar magnet geometry has a higher stray field than that of the four magnet surface sensor also presented, leading to a prohibitively short T2 eff. This means that the T1 values collected are notably shorter and not useful for distinguishing between clog state for the single magnet sensor. By contrast the four magnet surface sensor has a longer T2 eff, making it more suitable for T1 measurements; where T1= 915 ± 212 ms for a very thinly clogged sample, and T1= 127 ± 27 ms for a heavily clogged sample. This offers a clearly resolvable difference in the T1 values allowing the clogging state to be easily determined and making this sensor the desirable choice for long-term embedding.